Replacement names for four preoccupied talitrid genus-group names proposed by Lowry & Myers in 2019 (Crustacea, Amphipoda, Senticaudata) - Lowry, James K.; Myers, Alan A.; Nakano, Takafumi (Zootaxa, 2019)
A recent comprehensive review of the generic-level classification of the amphipod family Talitridae established 37 new genera (Lowry & Myers 2019). Among the 37 genus-group names, however, four names—Fleuria Lowry & Myers, 2019, Hurleyella Lowry & Myers, 2019, Tasmanella Lowry & Myers, 2019 and Wairua Lowry & Myers, 2019—are respectively preoccupied by the dipteran Fleuria Kieffer, 1924, the dipteran Hurleyella Runyon & Robinson, 2010, the brachiopod Tasmanella Laurie, 1991, and the arachnid Wairua Forster in Forster et al., 1990. Accordingly, new replacement names for each of the talitrid genus-group names are proposed herein. Additionally, the authorship of the superfamily Talitroidea cited in Lowry & Myers (2019) as Bulycheva, 1957, should be cited as Rafinesque, 1815.